Elements of Reading. - Heidmann, Mark (1999)
Keywords: dept.eng; faculty_collection; sabbatical_report

Poetry Does Theology: Chaucer, Grosseteste, and the Pearl-Poet. - Rhodes, James Francis (Spring;English., 1999)
Keywords: dept.eng; faculty_collection; sabbatical_report

[Poems for Crazy Quilt and Fair Haven] - Shipley, Vivian (Spring;English., 1999)
Keywords: dept.eng; faculty_collection; sabbatical_report

Annotated Edition of the Reading Notebooks of Virginia Woolf's Three Guineas. - Neverow, Vara (1996)
Keywords: dept.eng; faculty_collection; sabbatical_report

"Wynken de Worde" - Holbrook, Sue Ellen (1995)
Keywords: dept.eng; faculty_collection; sabbatical_report

Women Times Three. - Klein, Kathleen Gregory (1994)
Keywords: dept.eng; faculty_collection; sabbatical_report

My Mother Always Called Me by My Brother's Name. - Sabbatical Report - Ort, Daniel (1994)
Keywords: dept.eng; faculty_collection; sabbatical_report

(William Blake Anthology) - Rosso, G. A. (1994)
Keywords: dept.eng; faculty_collection; sabbatical_report

(English Composition Handbook) - Seidl, Alton (1994)
Keywords: dept.eng; faculty_collection; sabbatical_report

(Geoffrey Chaucer) - Rhodes, James Francis (1992)
Keywords: dept.eng; faculty_collection; sabbatical_report

(Meaning in Shakespearean Texts) - Shea, Michael (1992)
Keywords: dept.eng; faculty_collection; sabbatical_report

Rough Creek. - Shipley, Vivian (1992)
Keywords: dept.eng; faculty_collection; sabbatical_report

Topics in Poetry - Shipley, Vivian (Southern Connecticut State University?, 1995)
Keywords: Connecticut; New Haven; Southern Connecticut State University; College students' writings; American; dept.eng; faculty_collection

Understanding Things Fall Apart a Student Casebook to Issues, Sources, and Historical Documents - Ogbaa, Kalu (Greenwood Press, 1999)
Things Fall Apart is the most widely read and influential African novel. Published in 1958, it has sold more than eight million copies and been translated into fifty languages. African culture is not familiar to most American readers however, and this casebook provides a wealth of commentary and original materials that place the novel in its historical, social, and cultural contexts. Ogbaa, an Igbo scholar, has selected a wide variety of historical and firsthand accounts of Igbo history and cultural heritage. These accounts illuminate the historical context and issues relating to the c
Keywords: Achebe; Chinua. Things fall apart; Civilization; Sources; Igbo (African people) in literature; Igbo (African people); Nigeria; dept.eng; faculty_collection

Crazy Quilt - Shipley, Vivian (Hanover Press, 1999)
SCSU Faculty Scholar Award
Keywords: award_winner; dept.eng; faculty_collection

Blake, Politics, and History - DiSalvo, Jackie; Rosso, G. A.; Hobson, Christopher Z. (Garland Pub., 1998)
Keywords: 18th century; Politics and literature; 19th century; Political poetry; English; Blake; William; 1757-1827; Great Britain; History; History and criticism; Literature and society; History; Literature and history; History; Social problems in literature; Political and social views; Politics and literature; dept.eng; faculty_collection

You Can Write Poetry - Mock, Jeff (Writer's Digest Books, 1998)
Keywords: Authorship; Creative writing; Poetry; dept.eng; faculty_collection

Is This the End of Little Rico? - Ort, Daniel (Orchises, 1998)
Keywords: 20th century; Biography; Storytelling; Ort; Daniel; 1936-; Authors; American; dept.eng; faculty_collection

Floating - Troy, Robin (MTV : Pocket Books, MTV, 1998)
A woman whose husband is in jail has an affair with his brother, but the two discover too many differences and part. The novel, a debut in fiction, is based on the winning manuscript in a contest of some five hundred entries.
Keywords: Fiction; Fiction; Arizona; Fiction; Married women; Fiction; Mothers and sons; Prisoners' spouses; dept.eng; faculty_collection

Straight Man - Russo, Richard (Random House, 1997)
A comedy on university downsizing. To make sure the English department's budget is not cut, William Devereaux, its chairman, goes on TV threatening to kill a goose a day if that happens. Unfortunately a goose is beheaded soon after and Devereaux finds himself in hot water. The setting is Pennsylvania. By the author of Nobody's Fool.
Keywords: College teachers; Fiction; College stories; dept.eng; faculty_collection

How Many Stones?: Poems - Shipley, Vivian (Devil's Millhopper Press, 1997)
Keywords: Devil's Millhopper Press Chapbook Contest; dept.eng; faculty_collection

Devil's Lane - Shipley, Vivian (Negative Capability Press, 1996)
Keywords: dept.eng; faculty_collection

En Travesti: Women, Gender Subversion, Opera - Blackmer, Corinne E.; Smith, Patricia Juliana (Columbia University Press, 1995)
Keywords: Women in opera; Lesbianism; dept.eng; faculty_collection

The Woman Detective: Gender & Genre - Klein, Kathleen Gregory (University of Illinois Press, 1995)
Kathleen Gregory Klein traces female paid, professional private investigators in British, Canadian, and American novels, revealing that the detective novel is both a reflection of and potential barrier to social change for women. This edition adds sixty new female private eyes to the roster and includes an afterword that assesses the current state of the genre's new and old novels. A comprehensive bibliography and a character list update the field through mid-1994.–(Source of description unspecified.)
Keywords: Detective and mystery stories; English; English-speaking countries; History and criticism; Detective and mystery stories; American; History and criticism; Popular literature; History and criticism; Women detectives in literature; Women in literature; dept.eng; faculty_collection

Women Times Three: Writers, Detectives, Readers - Klein, Kathleen Gregory (Bowling Green State University Popular Press, 1995)
This volume explores the range of relationships among women writers, women detectives and women-centered mystery fiction, and women readers. Focusing on writers as diverse as Sara Paretsky, Joan Hess, Sarah Caudwell, P.D. James, Katherine V. Forrest, Mary Roberts Rinehart, Sue Grafton, D.R. Meredith, Dorothy L. Sayers, and Barbara Wilson, the authors analyze the development of detective fiction with a different agenda: the woman-authored woman detective. Examined through the eyes of actual and hypothetical women readers of the genre, these eleven essays concentrate new attention on the trio of reader, writer, and text when all three are modified by the terms "woman" and "mystery." The first essay collection to propose this gender and genre specific analysis, Women Times Three offers its readers a careful theoretical and critical investigation of both historical and contemporary models of consistently "new" mystery fiction., The essays' authors are not only widely published scholar-critics of mystery/detective fiction but also dedicated fans of the genre. Familiar with the full scope of mystery fiction, they bring insight and enthusiasm to their writing.
Keywords: 20th century; Women; Books and reading; Detective and mystery stories; American; English-speaking countries; English-speaking countries; Authors and readers; English-speaking countries; Feminism and literature; History; History and criticism; American fiction; History and criticism; Detective and mystery stories; English; History and criticism; English fiction; History and criticism; Women detectives in literature; Women and literature; Women authors; dept.eng; faculty_collection

Igbo - Ogbaa, Kalu (Rosen Pub. Group, 1995)
SCSU Faculty Scholar Award
Keywords: Igbo (African people); Juvenile literature; award_winner; dept.eng; faculty_collection

How to Publish and Win Writing Contests - Shipley, Vivian (Southern Connecticut State University?, 1995)
Keywords: Connecticut; New Haven; Southern Connecticut State University; College students' writings; American; dept.eng; faculty_collection

Latin Literature: A History - Conte, Gian Biagio (Johns Hopkins University Press, 1994)
Modern Language Association’s Scaglione Translation prize winner, SCSU Faculty Scholar Award
Keywords: Civilization; Historiography; Rome; History and criticism; Rome; In literature; Latin literature; SCSU Faculty Scholar Award; award_winner; dept.eng; faculty_collection

Great Women Mystery Writers: Classic to Contemporary - Klein, Kathleen Gregory (Greenwood Press, 1994)
A dictionary of over 117 women mystery authors giving details on their lives and their writing habits.
Keywords: Bibliography; Detective and mystery stories; American; Bio-bibliography; American fiction; Bio-bibliography; Detective and mystery stories; American; Bio-bibliography; Women and literature; Bio-bibliography; Women authors; American; Biography; Detective and mystery stories; English; Dictionaries; Dictionaries; Detective and mystery stories; English; Dictionaries; English fiction; Dictionaries; Women authors; English; English-speaking countries; Women authors; dept.eng; faculty_collection

The Gong and the Flute: African Literary Development and Celebration - Ogbaa, Kalu (Greenwood Press, 1994)
Keywords: African literature; History and criticism; dept.eng; faculty_collection

My Mother Always Called Me by My Brother's Name - Ort, Daniel (Orchises, 1994)
Keywords: 1971-; Ort; Daniel; 1936-; United States; Social life and customs; dept.eng; faculty_collection

Darvil: Prose Poems - Fort, Charles (St. Andrews Press, 1993)
Keywords: dept.eng; faculty_collection

Stranger Within - Hochman, Will (Mellen Poetry Press, 1993)
Keywords: dept.eng; faculty_collection

Blake's Prophetic Workshop: A Study of the Four Zoas - Rosso, G. A. (Bucknell University Press ; Associated University Presses, 1993)
Keywords: Blake; William; 1757-1827. Four Zoas; Prophecies in literature; dept.eng; faculty_collection

Gods, Oracles, and Divination: Folkways in Chinua Achebe's Novels - Ogbaa, Kalu (Africa World Press, 1992)
Keywords: Achebe; Chinua; Africa; Africa; Folklore; Folklore in literature; Folklore; In literature; Knowledge; dept.eng; faculty_collection

The Town Clock Burning: Poems - Fort, Charles (Carnegie Mellon University Press, 1991)
Keywords: dept.eng; faculty_collection

Ort Bran - Ort, Daniel (Orchises, 1990)
Keywords: dept.eng; faculty_collection

Oroonoko or the Royal Slave - Behn, Aphra (W.W. Norton, 1997)
Keywords: Behn; Aphra; 1640-1689. Oroonoko; Enslaved persons; Fiction; Slave trade; History; Sources; Slavery in literature; Suriname; dept.eng; faculty_collection

For Martin Luther King - Fort, Charles (Letters to America: Contemporary American Poetry on Race, 1995)
A collection of poems that explore the issues surrounding race relations in American society, told from the experience of Black, Native American, Asian, Arabic, Hispanic, and white cultures.–(Source of description unspecified.)
Keywords: 20th century; African Americans; American poetry; Poetry; Poetry; Race relations; Poetry; Racism; Poetry; United States; Race relations; dept.eng; faculty_collection

Roger & me: A review essay - Rosso, T. (Rethinking Marxism, 1990)
0 citations (Crossref) [2023-10-31]
Keywords: dept.eng

Hungary 1956 in the eyes of red diaper baby - Vegso, A.H. (Rethinking Marxism, 1990)
0 citations (Crossref) [2023-10-31]
Keywords: dept.eng

Contentious intimations: John Donne, Richard III, and the transgressive structures of seduction - Larocco, S. (Exemplaria, 1995)
0 citations (Crossref) [2023-10-31]
Keywords: dept.eng

A metacognitive approach to business communication case studies - Mceachern, Robert W (Business Communication Quarterly, 1999)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/012-744-482-351-599 tex.type: [object Object]
Keywords: dept.eng

Meeting minutes as symbolic action - Mceachern, Robert W (Journal of Business and Technical Communication, 1998)
Postmodern assumptions employed by some organizational theorists recognize that “administrators' greater power lies not in their ability to control resources but in their ability to manipulate symbols-the ceremonies, rituals, images, and language of the organization” (Graham and David 9). Thus, even a genre that is often considered neutral and objective, such as meeting minutes, can become a tool Of managerial control. This article presents data from an ethnographic case study that describes how an administrator in a theater organization manipulated language by using the minutes from a board of directors meeting to influence board members to vote to disband the organization.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/160-831-193-675-812 tex.type: [object Object]
Keywords: dept.eng

A medieval scientific encyclopedia "renewed by goodly printing"; Wynkyn de Worde's English De proprietatibus rerum. - Holbrook, Sue Ellen (Early Science and Medicine, 1998)
Wynkyn de Worde published c. 1495 the first printed edition of John Trevisa's English translation of an influential work of science composed by Bartholomew the Englishman in Latin in the thirteenth century, De Proprietatibus Rerum (DPR). The design of de Worde's book, the use of Latin in the rubrics, and the visual vocabulary of the illustrations bring readers of English into the circle of learning. First, the plan of organization of Bartholomew's encyclopedic work is analyzed and both that structure and the expository style of the work are related to memorial reading and use as a textbook. Next, the widespread use of DPR in Latin and vernacular languages is reviewed, the suggestion that certain of its books seem to have been used more than others is made, and the reliance of English readers, such as Roger Thorney, who commissoned de Worde's edition, on de Worde for learned books printed in their provincial tongue is pointed out. Finally, through comparison with certain manuscript and other printed editions, the methods de Worde used to make the book readable are explained, the layout is shown to support the idea of system, and the function of the pictures as visual texts carrying scientific ideas is demonstrated. © Koninklijke Brill NV, Leiden, 1998.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/083-374-886-228-212 tex.type: [object Object]
Keywords: Encyclopedias; Great Britain; History; 15th Century; History; Medieval; Printing; Science; Translations; United Kingdom; article; book; dept.eng; history; printing; publication; science

Women's work: The feminizing of composition - Holbrook, Sue Ellen (Rhetoric Review, 1991)
16 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/021-995-132-227-208 tex.type: [object Object]
Keywords: dept.eng